2023
DOI: 10.32604/cmc.2023.039883
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Equilibrium Optimizer for Solving Optimization Tasks

Yuting Liu,
Hongwei Ding,
Zongshan Wang
et al.

Abstract: The equilibrium optimizer (EO) represents a new, physics-inspired metaheuristic optimization approach that draws inspiration from the principles governing the control of volume-based mixing to achieve dynamic mass equilibrium. Despite its innovative foundation, the EO exhibits certain limitations, including imbalances between exploration and exploitation, the tendency to local optima, and the susceptibility to loss of population diversity. To alleviate these drawbacks, this paper introduces an improved EO that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The proposed EO variant was tested on 96 benchmark functions and 6 engineering optimization problems, comparing favorably against various advanced metaheuristic techniques. Finally, in [55], adaptive mechanisms, Cauchy perturbation, and cosine search strategies were introduced into EO to enhance the overall search capabilities of the algorithm. Testing on 15 classic test functions and the CEC 2017 benchmark test set demonstrated that the algorithm outperformed the comparison algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed EO variant was tested on 96 benchmark functions and 6 engineering optimization problems, comparing favorably against various advanced metaheuristic techniques. Finally, in [55], adaptive mechanisms, Cauchy perturbation, and cosine search strategies were introduced into EO to enhance the overall search capabilities of the algorithm. Testing on 15 classic test functions and the CEC 2017 benchmark test set demonstrated that the algorithm outperformed the comparison algorithms.…”
Section: Introductionmentioning
confidence: 99%